Sequencing re-defines Spiranthes relationships, with implications for rare and endangered taxa - Dueck, Lucy (Universidad de Costa Rica, 2015)
Species delimitation in the genus Spiranthes L.C. Richard (Spiranthinae, Cranichideae, Orchidoideae) has long been problematic, due mainly to morpholog- ical polymorphism confounded by hybridization and polyploidy, particularly in the S. cernua (L.) Rich. species complex (Correll 1950, Luer 1975, Sheviak 1982).